Long noncoding RNAs involved in therapeutic response: implications for cervical cancer drug resistance - Trujano-Camacho, Samuel; Contreras-Romero, Carlos; García-Castillo, Verónica; Sánchez-Marín, David; Olvera-Valencia, Mercedes; Rodríguez-Dorantes, Mauricio; Peralta-Zaragoza, Oscar; de León, David Cantú; López-Urrutia, Eduardo; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2025)
Cervical cancer (CC) remains among the top causes of death for women worldwide, especially in low-income countries, where screening strategies are less widespread. Treatment strategies are mainly based on DNA-damaging agents, though resistance mechanisms still pose a substantial challenge. Among the cellular components that mediate treatment resistance, long non-coding RNAs (lncRNAs) stand out because of their broad regulatory effects. They are involved in virtually all drug resistance mechanisms, such as drug efflux, DNA repair, evasion of cell death, and aberrant epigenetic modifications. Although resistance mechanisms are fundamentally similar in most cancers, the underlying regulatory networks vary substantially. Here, we review the literature for lncRNAs involved in treatment resistance mechanisms in general, and then focus on lncRNAs that mediate resistance in CC. We found a broad area of opportunity in lncRNA research in resistant CC, as the lncRNAs involved are still to be described. These master regulators are promising candidates for response markers and therapeutic targets. May this compilation serve as the basis for further descriptions of the regulatory roles of lncRNA in CC treatment resistance.